Principles of therapy and care of laboratory animals after chronic administration into Xylasine-Zoletyl® Anesthesia - Vovk AN; Karantysh GV; Kosenko PO; Medvedev DS (International Journal of Veterinary Science and Research - Peertechz Publications, 2020)
The use of a combination of dissociative anesthetics and alpha-2-agonists for chronic experiments in laboratory animals is advisable in the case of studying the functions of the limbic system. This requires the development of a protocol for withdrawing animals from this anesthesia, since frequent anesthesia leads to damage to organs and tissues, the need to increase the dose with frequent use of anesthesia, and distortion of the research results. This article provides recommendations for the elimination of chronic xylazine-Zoletil® anesthesia, including pharmacological therapy and additional care measures for experimental animals (based on a comparative analysis of changes in respiration on a pneumogram, the nature of dysfunctions during the period of anesthesia and the mortality rate of animals that were or did not use measures to withdraw from anesthesia).